Schnitzler syndrome: validation and applicability of diagnostic criteria in real‐life patients - Gusdorf, L.; Asli, B.; Barbarot, S.; Néel, A.; Masseau, A.; Puéchal, X.; Gottenberg, J‐E.; Grateau, G.; Blanchard‐Delaunay, C.; Rizzi, R.; Lifermann, F.; Kyndt, X.; et al. (Allergy (Copenhagen), 2017)
Background Schnitzler syndrome is characterized by an urticarial rash, a monoclonal gammopathy, and clinical, histological, and biological signs of neutrophil‐mediated inflammation. The aim of this study was to assess the applicability and validity of the existing diagnostic criteria in real‐life patients. Methods This multicentric study was conducted between 2009 and 2014 in 14 hospitals in which patients with Schnitzler syndrome or controls with related disorders were followed up. We compared the sensitivities and specificities and calculated the positive and negative predictive values of the Lipsker and of the Strasbourg criteria for the patients with Schnitzler syndrome and for the controls. We included 42 patients with Schnitzler syndrome, 12 with adult‐onset Still's disease, 7 with cryopyrin‐associated periodic disease, 9 with Waldenström disease, and 10 with chronic spontaneous urticaria. Results All patients with Schnitzler syndrome met the Lipsker criteria. According to the Strasbourg criteria, 34 patients had definite Schnitzler syndrome, five had probable Schnitzler syndrome, and three did not meet the criteria. One control met the Lipsker criteria and had probable Schnitzler syndrome according to the Strasbourg criteria. Sensitivity and specificity of the Lipsker criteria were 100% and 97%, respectively. For the Strasbourg criteria, sensitivity for definite and probable diagnosis was 81% and 93%, respectively, with a corresponding specificity of 100% and 97%. Conclusion Diagnostic criteria currently in use to diagnose Schnitzler syndrome are reliable. More investigations must be done to attest their efficiency in patients with recent‐onset manifestations.